THE CRUCIAL ROLE OF MENTAL PROCESSES IN THE DEVELOPMENT OF A CHILD'S SPEECH: INSIGHTS FROM SCIENTIFIC RESEARCH - Riskulova Aynura Urezali kizi (Journals Park Publishing, 2023)
This article delves into the multifaceted relationship between mental processes and the development of a child's speech. Drawing upon scientific research, it explores the influence of cognitive functions, social interactions, memory, socioeconomic factors, and neurological mechanisms on speech acquisition. The article also discusses interventions, therapy approaches, and future directions in the field of speech development, highlighting the implications of this research for education and clinical practices.
Keywords: Speech development, mental processes, cognitive functions, social interactions, memory, socioeconomic factors, neurological mechanisms, interventions, therapy approaches, language acquisition.